A novel locally resonant metastructure with soft-material rings for broadband and low frequency vibration attenuation. (1st December 2022) - Hao, Siting; Sheng, Hui; Lyu, Xiaofei; Ding, Qian
Highlights: Broadband gap in low frequency is obtained by the novel locally resonant metastructure. Calculation and verification methods include Gaussian expansion method, finite element method and experiment. The property of lightweight with resonable stiffness. Practical engineering applications in vibration attenuation in broad and low frequency. Abstract: Metastructure has been discovered as a new and effective means of vibration suppression in recent studies. Based on the basic principle of the locally resonant (LR) metastructure, a novel two-dimensional LR metastruture is proposed in this paper. The host plate is punched out several concentric holes and filled with soft materials, with the resonator installed in the center. The band structure of an infinite structure is calculated by using Gaussian expansion method as well as the finite element method. To further evaluate the vibration attenuation performance, the vibration transmission of a finite plate is obtained by both numerical and experimental methods. Formation mechanism of band gaps (BGs) is revealed by analyzing eigenmodes at boundary frequencies. The significance of the novel design is clarified from the mechanism level, about the characteristics of generating broad band gaps in low frequencies. The influence of both geometric parameters and material damping properties on BGs are discussed, including examples of a non-periodic plate and a periodic damped plate. Because of its features and simple design, it can be expected to be widely applied in engineering.